GASTROINTESTINAL PATHOLOGY IN SYSTEMIC SCLERODERMA (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Gastrointestinal tract (GIT) involvement holds an important place among the visceral manifestations of systemic scleroderma (SSc). Pathologies of the esophagus, stomach, small and large intestines can range from mild functional disorders to the development of pronounced chronic inflammation with mucosal metaplasia and dysplasia, formation of multiple erosions, hemorrhages, and deep ulcers. This review discusses the main clinical manifestations, diagnostic possibilities, and treatment of gastrointestinal involvement in systemic scleroderma.